Odpowiedzialność podmiotów zbiorowych za przestępstwa gospodarcze z perspektywy prawa polskiego oraz prawa niemieckiego (ujęcie prawno-porównawcze) - Popowicz-Pazdej, Anna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
The aim of this article is to depict the problem of corporates' liability for economic crimes. This issue will be presented from a comparative legal perspective taking into account Polish and German law. Firstly, in order to delimitate the research limits, the definition of economic crime with regard to the subject matter is presented. Defining the limits of the concept of economic crimes will then allow to explore the key issue – i.e. the analysis of the possibility of ascribing criminal liability to corporation. For many years, this issue has raised numerous controversies, especially in the legal systems of continental Europe. The implementation of relevant laws in Poland was dictated by the need to adapt to certain requirements of EU law. In Germany, such a legal concept already has been applied and was only slightly modified, although it is based on the administrative and criminal liability where financial sanctions can be imposed on a corporation when one of its officers has acted criminally on behalf of the corporation. Bearing in mind certain deficiencies of this concept, it has worked well in Germany for many years and despite few attempts to implement a new one, this concept ultimately remains the best solution. What is the most significant, it is without the detriment to the guilt theory.
Keywords: guilt; criminal liability; corporation; economic crimes; white-collar crimes